BUSINESS INTELLIGENCE OF THE NEW INNOVATIVE ENTERPRISE ECONOMY - S. YU. Kuznetsov (Real Economics Publishing House, 2014)
Business intelligence is a new management tool of an innovative enterprise. Business intelligence as a continuous innovation in business analytics of the new intellectual enterprise can integrate all activities into an efficient and sustainable business organization. BI promotes the prosperity of the firm, through intelligent management of strategies, finance, marketing, business processes, staff and assets in a world of unlimited information.